Karakteristik Geologi, Alterasi Hidrotermal Dan Mineralisasi Daerah Penyompa, Kecamatan Rantau Pulut, Kabupaten Seruyan, Provinsi Kalimantan Tengah. - Satriadi Abdullah; Arifudin Idrus; Nurkhamim Nurkhamim; Kris Ramlan; Arfan Siregar (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2023)
The characteristics of the ore deposit will be greatly influenced by the geological conditions of the area. Surface manifestations of an ore deposit can be identified by the presence of alteration and mineralization zones. The study of alteration zones and mineralization will assist in making an exploration plan for an ore deposit. The purpose of this study is to determine the geological conditions in more detail, and the potential for ore deposits in the study area by alteration, mineralization, and rock geochemistry. Field data collection techniques include geological mapping, and laboratory analysis includes geochemical analysis using the Fire Assay Atomic Absorption Spectrophotometry (FA-AAS) method. The study shows that the lithology of the study area is volcanic rocks composed of andesitic intrusive rocks, diorite rocks, granite rocks, and pyroclastic rocks in the form of breccias. Hydrothermal alteration that develops in the study area can be divided into four zones of alteration type, namely: silicification zone (quartz ± kaolin ± pyrite), argillic zone (kaolin ± quartz), inner propylitic zone (quartz ± chlorite ± epidote ± albite ± pyrite), and outer propylitic zone (quartz ± chlorite ± epidote). Based on the lithology and type of alteration found, it is known that the type of deposit in the study area is part of Cu-Au porphyry deposits in the retrograde and post-mineral alteration stages based on the model of Corbett (1854). Mineralization potential in the study area includes pyrite-sulfide potential, hematite potential with paramagnetic properties, and hematite oxide potential. The results of the geochemical analysis showed that the research area had the highest levels of 0.02 ppm Au, 0.8 ppm Ag, 20 ppm Cu, and Fe <100 ppm.